Some Integral Inequalities for n-Polynomial ζ-Preinvex Functions - Shanhe Wu; Muhammad Uzair Awan; Muhammad Ubaid Ullah; Sadia Talib; Artion Kashuri (Journal of Function Spaces)
In this paper, we study the properties of n-polynomial ζ-preinvex functions and establish some integral inequalities of Hermite-Hadamard type via this class of convex functions. Moreover, we discuss some special cases which provide a significant complement to the integral estimations of preinvex functions. Applications of the obtained results to the inequalities for special means are also considered.